Social media and industrial action: new tools for trade union activity - Ornella La Tegola (Labour & Law Issues, 2019)
In an economic system now dominated by digital interconnection, the toolbox of trade union activity risks being not only obsolete but also rusty. In the era of the Internet and technological innovation, the classic forms of protest alone are not enough. The protection of workers’ rights passes today through the possibility of the union to exploit the ability of the web to amplify the echo of the claim and, at the same time, to affect the employer need to maintain or gain a positive reputation among consumers.